Angiopoietin-Like Protein 4 May Be an Interplay Between Serum Uric Acid and Triglyceride-Rich Lipoprotein Cholesterol - Peng, Yani; Hu, Die; Luo, Qingting; Peng, Daoquan (Frontiers in Cardiovascular Medicine, 2022)
Background Although the available evidence has indicated a link between elevated serum uric acid (SUA) level and dyslipidemia, the potential contribution of SUA on lipid profiles remains unclear. Experimental and clinical studies have revealed several mechanisms through which high serum angiopoietin-like protein 4 (ANGPTL4) level exerts deleterious effects on lipid metabolism, but the role of ANGPTL4 in SUA-associated dyslipidemia has not been well studied so far. Methods Eighty subjects were classified into high SUA group (n=40) and low SUA group (n=40) by the median value of SUA in the whole study population. Serum ANGPTL4 levels were determined by enzyme-linked immunosorbent assays. Results In our study, we observed that not only serum triglyceride level [1.03(0.78,1.50) mmol/l vs 1.59(1.18,2.37) mmol/l, P=0.001] but also serum triglyceride-rich lipoprotein cholesterol (TRL-C) level [0.38(0.32,0.45) mmol/l vs 0.46(0.34,0.54) mmol/l, P=0.012] were significantly elevated in high SUA group. Additionally, serum ANGPTL4 in high SUA group was higher than in low SUA group [15.81(11.88,20.82) ng/ml vs 22.13(17.88,32.09) ng/ml, P=0.000]. Moreover, in all subjects, TRL-C levels were positively associated with SUA (r=0.26, P=0.023, n=80) and ANGPTL4 levels (r=0.24, P=0.036, n=80). Using stepwise multiple regression analysis to adjust for potential confounders, SUA was discovered to be an independent contributor to serum ANGPTL4 (P=0.023). At the same time, serum ANGPTL4 was an independent contributor to the level of TRL-C (P=0.000). However, the correlation between SUA and TRL-C disappeared after controlling for ANGPTL4 level. Conclusion SUA was positively correlated to triglyceride-rich lipoprotein cholesterol (TRL-C). ANGPTL4 may be an interplay between SUA and associated elevation of TRL-C.